2017
DOI: 10.1002/acr.22944
|View full text |Cite
|
Sign up to set email alerts
|

Persistence With Conventional Triple Therapy Versus a Tumor Necrosis Factor Inhibitor and Methotrexate in US Veterans With Rheumatoid Arthritis

Abstract: ObjectiveTo compare persistence and adherence to triple therapy with the nonbiologic disease‐modifying antirheumatic drugs (DMARDs) methotrexate (MTX), hydroxychloroquine, and sulfasalazine, versus a tumor necrosis factor inhibitor (TNFi) plus MTX in patients with rheumatoid arthritis (RA).MethodsAdministrative and laboratory data were analyzed for US Veterans with RA initiating triple therapy or TNFi + MTX between January 2006 and December 2012. Treatment persistence 365 days postindex was calculated using 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 50 publications
(58 reference statements)
1
26
0
Order By: Relevance
“…In summary, this observational cohort study demonstrated that in US veterans with RA, persistence and adherence rates remained relatively low when escalating from MTX to combination MTX‐TNFi and triple therapy, findings that mirror a larger recent study published by our group involving a larger cohort of US veterans . However, the current study also helped elucidate via chart abstraction the reasons why patients discontinue their combination medications for their RA.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…In summary, this observational cohort study demonstrated that in US veterans with RA, persistence and adherence rates remained relatively low when escalating from MTX to combination MTX‐TNFi and triple therapy, findings that mirror a larger recent study published by our group involving a larger cohort of US veterans . However, the current study also helped elucidate via chart abstraction the reasons why patients discontinue their combination medications for their RA.…”
Section: Discussionsupporting
confidence: 80%
“…However, our findings are consistent with a prior study by Bonafede et al , in which persistence rates were 29.4% for MTX‐TNFi and 23.2% for triple therapy at 1 year, and adherence rates were 27.9% for MTX‐TNFi versus 18.2% for triple therapy. Other studies have shown relatively low adherence to RA treatment in real‐world clinical practice, including a recent publication by our group, using a larger cohort of US veterans . Lower persistence and adherence rates represent a greater extent of unrealized treatment benefit and poorer clinical outcomes in RA.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Since the publication of these results, questions have surfaced regarding adherence and durability of triple therapy. Results from 2 separate retrospective studies using administrative data from the Veterans Affairs (VA) health system (a major source of RACAT trial participants) have suggested that patients taking triple therapy have lower adherence and lower treatment persistence than patients on methotrexate‐TNF inhibitor , for former observations contrasting with similar adherence rates reported from RACAT . The present study is an open‐label followup to the RACAT trial and explores the subsequent durability of triple therapy versus methotrexate‐etanercept in randomized patients following completion of the 48‐week double‐blinded study.…”
Section: Introductionmentioning
confidence: 90%